Konstruksi gender dalam problematika childfree di sosial media Twitter - Mingkase, Nursyamsiah; Rohmaniyah, Inayah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2022)
Women's roles and feminine identities have historically and traditionally been built around motherhood. However, in recent years there has been a growing trend of childfree (without children) educating people about not parenting as a legitimate life choice through qualitative methods with virtual ethnographic studies. Analyzing Twitter tweets using the social construction theory of Peter L. Berger and Thomas Luckmann through a gender perspective, this paper aims to review gender construction in childfree problems where this choice is still considered taboo in the public sphere. Being Childfree allows having a positive identity oneself as an autonomous, rational, and responsible decision-maker. At the same time, rejecting that choice allows someone who cannot choose child-free (for various reasons) to have a flawless identity regarding deviations from the norm of parenthood. Although childfree is still only known in Indonesia as a whole or a broader context, childfree has been practiced by several people in a private space. However, this choice is against the culture of society where the family is considered an essential component in the life cycle; many do not feel the need or do not dare to speak up. Not only non-natural differences, gender construction that places women's nature at the biological level is also problematic. The nature of women who have a uterus is required to function correctly so that child-free decisions are considered deviant and abnormal.